Bridging Knowledge: The Role of Preservation Materials in Safeguarding Library Collections and Enhancing Cultural Continuity - Barman, Mr.Shyamapada; Singh, Dr. Dharam Vir (CENTRAL ASIA AND THE CAUCASUS, 2024)
Libraries have long been the custodians of humanity’s collective knowledge, safeguarding cultural, historical, and intellectual heritage for future generations. However, the passage of time, environmental factors, and human handling pose significant threats to the longevity of library collections, which often include rare manuscripts, historical documents, and fragile artifacts. Preservation materials are essential tools in addressing these challenges, offering effective solutions to mitigate decay and deterioration (American Library Association, 2020). Acid-free papers, archival boxes, protective films, and deacidification sprays are some of the specialized materials that play a critical role in maintaining the integrity of collections. These materials are designed to counteract environmental and chemical factors that cause damage, ensuring that books, documents, and other resources remain accessible for centuries